Spatiotemporal characterization of the isotopic composition of meteoric waters in Cuba - Alejandro Garcia-Moya; Carlos Manuel Alonso-Hernández; Ricardo Sánchez-Murillo; Yasser Morera-Gómez; Minerva Sánchez-Llull; Oscar Díaz Rizo; Osvaldo Cuesta Santos; Rosemery López Lee; Osvaldo Brígido Flores; Enma Odalys Ramos Viltre; Lucia Ortega (Scientific Data)
Abstract The stable isotope composition of meteoric water has been widely used to understand hydrological processes worldwide. We present a unique dataset, with the isotopic composition (δ18O and δ2H) of meteoric waters, derived from a nationwide study in Cuba. It includes monthly composite and event-based precipitations, from January 2017 to December 2021 (N = 526 and N = 111 respectively). Monthly data showed minor seasonal trends (dry vs. rainy), with a notable influence of tropical cyclones. Event-based data demonstrated that precipitation associated with tropical cyclones exhibited lower isotopic compositions. The analysis of potential factors influencing the isotopic composition of precipitation showed a minor influence of the rainfall amount, but negligible influence of factors such are relative humidity, elevation, and air temperature. This data set can be used as a tool not only to understand hydrological processes at the country scale, but also to further improve and develop isotope-enabled modelling for assessing water balances and fluxes, understanding the impact of extreme events, and paleoreconstruction in the Intra-Americas Sea.